Avaliação e desempenho de juntas soldadas pelo processo GMAW - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Welding is the process of joining metals by melting. This process evolved throughout the twentieth century, having several variations and adaptations according to the technological advance, going from a manual to robotized process. GMAW (Gas Metal Arc Welding) welding is a widely used process in industries, being carried out through an electric arc between the part and the consumable in wire form, in which the uncoated electrode is supplied through a continuous feeder. The protective gas, inert or not, protects the cord from impurities, avoiding possible defects of the material. This process is inexpensive and allows to be easily automated, and also allows to weld diverse types of steels. When done well, GMAW soldering has good performance and there is no slag compared to other more common processes used in the industry. This work evaluates the performance of welded joints by joining SAE 1030 steel sheets of different thicknesses (1.8 mm, 2 mm, 2.25 mm, 2.5 mm and 2.65 mm) in automatic equipment, made by the company PS Zamprogna, from Canoas/RS. The machine used is Starweld 390x3, electrode ER70S-6, inert gas with 75% CO2 and 25% Ar. The welding was performed in one pass, by the equipment at a constant speed for diferente thicknesses. To analyze the weld, tensile, microhardness and micrograph tests were carried out to evaluate the mechanical strength, hardness, toughness and to identify possible defects in the structure at micro and macro level. After analysis of the results, it was identified that the high temperature gradient, which led to the growth of coarse grains, low hardness and rupture in the weld (in the tensile test), which compromises the same. For thicker joints (1.8 mm and 2 mm) this gradient was more severe, where it was observed the appearance of cracks at the microstructural level. For thicker joints (2.25 to 2.65), the weld had good behavior in the tensile test, and microhardness and micrograph results were in agreement with the literature.
Keywords: Engenharia mecânica; Soldagem; Desempenho; GMAW; Mechanical Engineering; Performance; Welding; CNPQ::ENGENHARIAS